Neuroprotective effects on microglia and insights into the structure–activity relationship of an antioxidant peptide isolated from Pelophylax perezi - Plácido, Alexandra (2022)
© 2022 The Authors. Journal of Cellular and Molecular Medicine published by Foundation for Cellular and Molecular Medicine and John Wiley & Sons Ltd. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited